Aberrant intrinsic neural network strength in individuals with “smartphone addiction”: an MRI data fusion study - Schmitgen, Mike; Wolf, Nadine D.; Sambataro, Fabio; Hirjak, Dusan; Kubera, Katharina Maria; Koenig, Julian; Wolf, Robert Christian (Brain and behavior, 2022)
Background and objectives Excessive smartphone use, also referred to as “smartphone addiction” (SPA), has increasingly attracted neuroscientific interest due to its similarities with other behavioral addictions, particularly internet gaming disorder. Little is known about the neural mechanisms underlying smartphone addiction. We explored interrelationships between brain structure and function to specify neurobiological correlates of SPA on a neural system level. Methods Gray matter volume (GMV) and intrinsic neural activity (INA) were investigated in individuals with SPA (n = 20) and controls (n = 24), using multimodal magnetic resonance imaging and multivariate data fusion techniques, that is, parallel independent component analysis. Results The joint analysis of both data modalities explored shared information between GMV and INA. In particular, two amplitudes of low frequency fluctuations-based independent neural systems significantly differed between individuals with SPA and controls. A medial/dorsolateral prefrontal system exhibited lower functional network strength in individuals with SPA versus controls, whereas the opposite pattern was detected in a parietal cortical/cerebellar system. Neural network strength was significantly related to duration of smartphone use and sleep difficulties. Discussion and conclusions We show modality-specific associations of the brain's resting-state activity with distinct and shared SPA symptom dimensions. In particular, the data suggest contributions of aberrant prefrontal and parietal neural network strength as a possible signature of deficient executive control in SPA. Scientific significance This study suggests distinct neural mechanisms underlying specific biological and behavioral dimensions of excessive smartphone use.